Insight into the phytochemical, biological, and in silico studies of Erythrina suberosa roxb.: A source of novel therapeutic bioactive products from a medicinal plant. (April 2023) - Alamri, Abdulhakeem S.; Saleem, Hammad; Pervaiz, Irfan; Khurshid, Umair; Butt, Juwairiya; Chohan, Tahir Ali; Alhomrani, Majid; Locatelli, Marcello; Zainal Abidin, Syafiq Asnawi; H Alqahtani, Yasir Nasser; Rengasamy, Kannan R.R.; Mahomoodally, Mohamad Fawzi
Abstract: Background: Erythrina suberosa (E. suberosa) Roxb. also known as corky coral tree is used as a folklore medicine to treat ulcers and piles. This study explored the phytochemical profiles of methanol and dichloromethane (DCM) extracts from the aerial, root, and flower parts of E. suberosa . Method: Total bioactive contents, high-performance liquid chromatography array (HPLC-PDA) polyphenolic quantification, and ultra-high performance liquid chromatography-mass spectrometry (UHPLC-MS) analysis were used to evaluate the phytochemical profile. Biological potential was evaluated by determining their antioxidant (DPPH, ABTS, FRAP, CUPRAC, Phosphomolybdenum, and metal chelating) and enzyme inhibitory (cholinesterase, amylase, glucosidase, and tyrosinase) effects. Results: The phenolic (46.26 mg GAE/g extract) and flavonoid (32.46 mg QE/g extract) contents were found to be highest in the methanolic extract of roots (EsR-M). HPLC-PDA analysis determined the presence of numerous bioactive compounds, including catechin, syringic acid, p -hydroxy benzoic acid, gallic acid, vanillic acid, epicatechin, rutin, chlorogenic acid, carvacrol, sinapinic acid, and naringenin in considerable amounts. A total of 143 phytochemicals, belonging to phenolic, flavonoid, coumarin, terpenoid, chalcone, saponin, and glycoside classes, were tentatively identified by UHPLC-MS analysis. Aerial methanolic extract (EsA-M) exhibited highest radical scavenging (DPPH 86.81 mgTE/g extract, ABTS 245.17 mgTE/g extract) as well as reducing potential (FRAP 177.12 mgTE/g extract, CUPRAC 177.12 mgTE/g extract). Likewise, it was also noted to be most active for BChE (5.70 mg GALAE/g extract) and tyrosinase inhibition (148.35 mg KAE/g extract). While, roots-DCM extract (EsR-D) presented considerable inhibition for AChE (4.69 mg GALAE/g extract) and amylase (0.81 mmol ACAE/g extract) enzymes. Coreopsin, davallioside A, and isovitexin were docked to tyrosinase to depict possible interaction. Conclusion: This study has established baseline data on the biological and phytochemical profile of E. suberosa which was found to possess antioxidant and enzyme inhibition properties which tend to validate its traditional uses. However, further studies to identify the molecular targets responsible for these activities are warranted which could be explored as a functional food. Graphical abstract: Image 1 Highlights: Erythrina suberosa is a food plant used traditionally against several diseases. Phytochemical, antioxidant, and enzyme inhibitory activities of extracts were undertaken. The extract possessed bioactive compounds and with potent biological activities. Molecular docking highlighted interaction between the key phytochemicals against targeted enzymes.